Cortical neural activity during responses to mechanical perturbation: Effects of hand preference and hand used - Kevin Hooks; Kimia Kiani; Qiushi Fu (NeuroImage)
Handedness is an important feature of human behavioral lateralization that has often been associated with hemispheric specialization. Existing neuroimaging research on the effect of handedness during motor control has focused on well-practiced or predictable tasks, but not tasks that involve unpredictable perturbations. We examined the extent to which handedness (measured by self-reported hand preference) and whether the dominant hand is used or not influence the motor and neural response during unimanual voluntary corrective actions. The experimental task involved controlling a robotic manipulandum to move a cursor from a center start point to a target presented above or below the start. In some trials, a mechanical perturbation of the hand was randomly applied by the robot either consistent or against the target direction, while electroencephalography (EEG) was recorded. Fourteen left-handers and fourteen right-handers completed the experiment. Left-handed individuals had a greater negative peak in the frontal event-related potential (ERP) during the initial voluntary response stage (N140) than right-handed individuals. Furthermore, left-handed individuals showed more symmetrical ERP distributions between two hemispheres than right-handed individuals in the frontal and parietal regions during the late voluntary response stage (P380). To the best of our knowledge, this is the first evidence to demonstrate the differences in the cortical control of voluntary corrective actions between left-handers and right-handers.